E-MuLearn: design de cenários de aprendizagem para museus virtuais baseado em personas - Welter, Eline Faliane de Araújo (2016)
The use of technology to improve the process of teaching and learning is a well-known practice, young people have shown increasing interest in the use of computers and mobile devices as support classes. To encourage this practice, several pedagogical activities can be performed via Internet. However, to contribute to the teaching of History and spread of Culture and Art, museums have sought space in virtual environments. From this premise, it was observed that virtual museums can be seen as an important tool in the teaching and learning process. The aim of this work is to propose a cycle to help create learning scenarios from elements of a museum, based on personas technique to support the teaching of History or a related field. In the first part of the study, Action Research methodology was adopted to carry out the investigation process by the teachers, museums expert and students; to verify the viability of the use of learning scenarios. The AR1 was conducted with 14 teachers and 1 museum expert to verify the feasibility of creating a learning scenario from museum elements. Already AR2 was conducted with 174 elementary school students, to verify the acceptance of learning scenarios. One of the results identified by the AR1 were the artifacts required to compose learning scenarios. However, there was a need for a device to aid in building the persona. For this, there was an adjustment in the empathy map technique called MapLearn as teacher support during the persona construction process. It has also been identified the need to create a cycle to support teachers and museum experts for the creation of learning scenarios. The validation of the proposal included the evaluation of MapLearn; cycle e-MuLearn; and learning scenarios, through 2 case studies and a controlled experiment. The analyses showed that the cycle e-MuLearn and their artifacts can contribute to creation of learning scenarios to support teaching of History.